Combination of Dental Pulp Stem-Cell Secretome and Robusta Coffee Bean Extract (Coffea canephora) in Enhancing Osteocalcin and Alkaline Phosphatase Expression in Periodontitis-Induced Wistar Rats - Millenieo Martin; Desi Sandra Sari; Roslian Ayu Mantika; Depi Praharani (Wolters Kluwer Medknow Publications, 2021)
Introduction: Indonesia riches with many beneficial herbal ingredients; one of them is coffee obtained from Jember which has antibacterial and anti-inflammatory properties for treating periodontitis. Meanwhile, dental pulp stem cells (DPSCs) during culture secrete various advantageous secretome for tissue regeneration. This investigation intended to examine the expression of osteocalcin (OCN) and alkaline phosphatase (ALP) after the administration of the combination between DPSC secretome and the Robusta coffee bean extract (RCBE) in periodontitis-induced animal model. Materials and methods: Thirty-five Wistar rats were randomly selected and divided into seven groups accordingly; group K0, group K1-7 (untreated periodontitis rats for 7 days), group K1-14 (untreated periodontitis rats for 14 days), group K2-7 (periodontitis rats administered with RCBE for 7 days), group K2-14 (periodontitis rats administered with RCBE for 14 days), group K3-7 [administered with both RCBE and stem-cell secretome (SCS) for 7 days], and group K3-14 (administered with both RCBE and SCS for 14 days). Periodontitis was induced by implementing wire installed in the rat's first mandibular molar. The combination of RCBE and DPSC secretome was administered intrasulcus in the rat's first mandibular molar gingiva. Moreover, least significant difference was performed after the analysis of variance test to investigate the significant difference between groups (P < 0.05). Results: The highest OCN and ALP were expressed in group K3-14, whereas the lowest OCN expression was found in K1-7 group and lowest ALP expression was displayed in K0 group. Additionally, there was significant difference in OCN and ALP between groups. Conclusion: The administration of the combination between dental pulp stem-cell secretome and RCBE (Coffea canephora) can enhance OCN and ALP expression as documented immunohistochemically.